Malignant Melanoma on a Thermal Burn Scar with an Interval of More Than 70 Years - Shusuke Uchida; Naoki Oiso; Kuriko Shiga; Tomohiko Narita; Akira Kawada (Karger Publishers, 2016)
Cases of malignant melanoma on thermal burn scars have occasionally been reported. We report a 78-year-old Japanese female with malignant melanoma on a thermal burn scar with an interval of more than 70 years. Our case reemphasizes the importance of regular examinations in persons with thermal burn scars.